2018
DOI: 10.1002/adom.201701402
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of Plasma Carriers in Graphene: An Approach by Frequency‐Dependent Optical Conductivity Measurement

Abstract: resulting in ultrahigh carrier mobilities, long mean free paths, and anomalous quantum Hall effects. [3][4][5][6][7] The most important advantage of graphene is the tunability of the carrier densities, which can be easily controlled by a gate bias or doping. [8][9][10][11][12] Consequently, graphene has been applied as convenient tunable terahertz (THz) metamaterials. [9,10,13,14] In photonics, the optical properties of graphene have been discussed with the surface plasmon model, corresponding to the Drude mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Nanoribbons with variable width were prepared by optical lithography and oxygen plasma etching: the frequency of the observed localized plasmons was shown to depend on the ribbon dimensions and on the doping. Choi et al [209] used microwave dielectric loss Adv. They showed that substrate terraces and wrinkles on the graphene surface due to strain relaxation during annealing serve as confining potential for carriers and can be also used to excite THz localized plasmons.…”
Section: Thz Properties Of Graphenementioning
confidence: 99%
“…Nanoribbons with variable width were prepared by optical lithography and oxygen plasma etching: the frequency of the observed localized plasmons was shown to depend on the ribbon dimensions and on the doping. Choi et al [209] used microwave dielectric loss Adv. They showed that substrate terraces and wrinkles on the graphene surface due to strain relaxation during annealing serve as confining potential for carriers and can be also used to excite THz localized plasmons.…”
Section: Thz Properties Of Graphenementioning
confidence: 99%
“…The intraband relaxation of the injected electron exhibits multiple pathways on ultrafast time scales, such as down to the MoS 2 conduction band minimum (CBM) at the K and M points, because all of these processes are ultrafast, ranging from 150 fs to (sub-) 1 ps. , Then, it transfers back and recombines with the hole residing on the graphene. The K–K transition should be slow because it occurs across a wide energy gap, evidenced by the calculated MoS 2 CBM population decay taking place over 230 ps (Figure S1), which is 2–3 orders of magnitude longer than the experimentally reported time scales. Alternatively, the M–K transition becomes dominant due to the presence of multiple intermediate states between the M and K points (Figure a).…”
mentioning
confidence: 99%
“…On the other hand, the increased carrier density can be attributed to an increase in oxygen adsorption on the graphene surface following plasma treatment, as reported in earlier studies. [12,17,18] Keeping in mind the very low power and plasma exposure time, XPS studies were carried out to confirm if indeed such an increase in oxygen bonding on the graphene surface occurred. In addition, since exposure to H2 plasma is expected to act in an opposite way to O2 plasma exposure, we also performed electrical and XPS characterization on H2 plasma treated graphene samples, and the XPS spectra and carrier transport characteristics were compared between initially untreated, O2 plasma treated, and H2 plasma treated graphene.…”
Section: Resultsmentioning
confidence: 99%